Enseigner et apprendre en présentiel - Liudmyla Holubnycha; Tetiana Shchokina; Natalia Soroka
The article deals with the traditional format of teaching and learning from the point of view of its quality, in particular the advantages and disadvantages of face-to-face education in comparison with online training. The purpose is to check whether the classroom training process is of better quality than online teaching and learning on the basis of the real case of teaching English at Yaroslav Mudryi National Law University. The tasks are to find out the pluses of offline training in comparison with the online format; to reveal the minuses of the traditional educational form in comparison with the online format on the basis of real teaching experience; and to check whether the pluses or the minuses of offline training have a greater influence on intermediate students' learning results. The investigation methods are empirical methods (surveys, observation) and general theoretical methods (analysis, syntheses and comparison). The results exposed the following: 1) benefits of face-to-face training: real-time interaction, improvement of social skills, collaboration, organization, motivation, accessibility, and better assessment; 2) cons of face-to-face training: processing a smaller capacity of programme material; problems with discipline; impossibility of listening to the lesson material repeatedly if necessary; problems with access to learning material from the internet; and the tendency of some students to have a psychological barrier to speaking a foreign language "live" in front of other students; and 3) the intermediate students' learning results demonstrated that offline students have worse academic progress than the students studying online. The conclusion is that the minuses of offline training have a greater influence on students' learning results than the pluses do. In order to conclude which format of education is of better quality, it is necessary to continue investigating the problem.